Family Communication Patterns on the Mental Health of Children from Divorced Families - Nurhermaya, Amalia Rahma; Harahap, Farida (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
Studies show that children from divorced families tend to experience long-term psychological problems, including depression and difficulties in forming social relationships. This study aims to explore how parental divorce can affect children's mental health based on the experiences of four subjects who grew up in divorced families. The results show that divorce has a profound impact, especially during adolescence. The research design used in this study was qualitative phenomenology, conducting semi-structured interviews with four subjects. Several subjects experienced difficulties in adjusting and interacting in their social environment. Emotional closeness does not only depend on how often children communicate with their parents but can also be influenced by direct interaction. The reasons for divorce include incompatibility, differences in lifestyle, and irresponsibility of one of the parents, which are significant triggering factors. The results of this study highlight that the way children communicate with their parents has an influence on how they cope with the impact of divorce and the importance of emotional and social support in the adjustment process. The implication of these findings is that researchers, communities, and parents need to work together to create a supportive environment so that children can adapt to change and reduce the negative impact of divorce.Studi menunjukkan bahwa anak-anak dari keluarga yang bercerai cenderung mengalami masalah psikologis jangka panjang, termasuk depresi dan kesulitan dalam menjalin hubungan sosial. Penelitian ini bertujuan menggali bagaimana perceraian orang tua dapat mempengaruhi kesehatan mental anak pada pengalaman empat subjek yang tumbuh dari latar belakang keluarga bercerai menunjukan bahwa perceraian memberikan dampak yang mendalam, terutama pada masa remaja. Desain metode penelitian yang digunakan dalam penelitian ini adalah kualitatif fenomenologi dengan melakukan wawancara semi terstruktur dengan subjek sebanyak 4 orang. Beberapa subjek mengalami pengaruh dalam menyesuaikan diri dan berinteraksi dilingkungan sosial. Kedekatan emosional tidak hanya bergantung pada seberapa sering anak berkomunikasi dengan orang tua namun dapat dipengaruhi oleh interaksi secara langsung. Alasan perceraian yang terjadi diantaranya, ketidakcocokan, perbedaan gaya hidup dan ketidaktanggung jawaban dari salah satu orang tua menjadi faktor pemicu yang signifikan. Hasil penelitian ini menyoroti bahwa cara anak berkomunikasi dengan orang tua memiliki pengaruh pada bagaimana cara anak mengatasi dampak perceraian serta pentingnya dukungan emosional dan sosial dalam proses penyesuaian. Implikasi temuan ini dari peneliti yakni masyarakat dan orang tua perlu bekerja sama untuk menciptakan lingkungan yang mendukung agar anak-anak dapat beradaptasi dengan perubahan dan mengurangi dampak negatif dari perceraian.